T helper cell unresponsiveness: rapid induction in antigen-transgenic and reversion in non-transgenic mice. - Bachmann, M; Rohrer, U; Steinhoff, U; Bürki, K; Skuntz, S; Arnheiter, H; Hengartner, H; Zinkernagel, R (1994)
T cell tolerance is usually established by clonal deletion of self-specific T cells in the thymus, or some times, in the periphery. Alternatively, tolerance may also be achieved by induction of clonal T cell unresponsiveness by a poorly understood mechanism called "anergy". We found that transgenic mice expressing a soluble form of vesicular stomatitis virus (VSV) glycoprotein (G) predominantly in liver and kidney exhibited normal B cell responses. VSV-G-specific T help-independent neutralizing IgM responses were within normal ranges, but no T help-dependent neutralizing IgG antibodies were generated upon immunization with recombinant VSV-G protein and recombinant vaccinia virus expressing VSV-G. This demonstrated absence of B cell tolerance but presence of T helper cell unresponsiveness. After adoptive transfer of transgenic spleen cells into thymectomized immuno-incompetent hosts, the unresponsive T helper cells regained function and switched the neutralizing IgM response to IgG, comparably to control T helper cells, within 7 days. Conversely, when naive non-transgenic spleen cells were transferred into transgenic mice, VSV-G-specific T helper cells became unresponsive within 3-4 days. These results suggest that VSV-G-specific T helper cells are rendered unresponsive within a few days in the VSV-G transgenic host also outside of the thymus and that this unresponsiveness was reversed by transfer into antigen-free recipients.